(3GbJaGA GdCKQ HYO PgGH Cgd GdCKQs - (3YHO Gddg Hf eMeO Hf CHj HcQ GdYjGTj, CHh SGde,J (B1090 (3g` s ((3eMeO GdObGb Hf CMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef GSJfO Edjg hUd hef EfbWY Edjg GJUd s
(3BNQgG (B:s
(3hgPG BNQ eG bUOJ PcQg eY TZd GdHGd hUdi Gdg Ydi SjOfG eMeO hQGdUMH hGdBd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B6 - (3U(B45s
(3fSNI Yf fSNI GdeDda GdJj ocJHJ SfI (B1068(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B129 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B112s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B42 s
Keywords: (3GdJGQjNs